Component Analysis and Antiangiogenic Activity of Thailand Stingless Bee Propolis - Ishizu, Eriko; Honda, Sari; Ohta, Tosihro; Vongsak, Boonyadist; Kumazawa, Shigenori (UI Scholars Hub, 2019)
Propolis is a natural resin produced by honey bees from certain plants, has gained popularity as a food and alternative medicine. However, to the best of our knowledge, few studies on native Thailand stingless bee propolis are available. Information on the chemical composition and biological activities of propolis is needed to investigate its potential utility. Recently we have reported the possible plant origin of Thailand stingless bee propolis, Garcinia mangostana. In this study, further component analysis, functional evaluation, and identification of the plant origin of Thailand stingless bee propolis are conducted. Nine xanthones, including α-mangostin, garcinone C, γ-mangostin, cochinchinone T, β- mangostin, gartanin, 8-deoxygartanin, 9-hydroxycalabaxanthone, and mangostanol, were identified from the propolis. Comparative analysis of 70% ethanol extracts of Thailand stingless bee propolis (EEP) and the yellow resin from the fruit surface of G. mangostana (EEM) was performed using LC-MS, and similar chromatographic patterns were obtained. This result suggests that the plant origin of Thailand stingless bee propolis is confirmed to be the yellow resin from the fruit surface of G. mangostana. EEP and EEM were then tested for their ability to inhibit the tube formation of human umbilical vein endothelial cells, and both samples inhibited the tube formation of these cells in a concentrationdependent manner. This result indicates that Thailand stingless bee propolis may have future applications in the prevention and treatment of angiogenesis-related diseases.